Adherence to Exercise Prescription and Improvements in the Clinical and Vascular Health of African Americans - BABBITT, DIANNE M. (Int J Exerc Sci, 2017)
Improvements in indices of vascular health and endothelial function have been inversely associated with hypertension, a risk factor for cardiovascular disease (e.g., myocardial infarction, stroke, and heart failure), renal failure, and mortality. Aerobic exercise training (AEXT) has been positively associated with improvements in clinical health values, as well as vascular health biomarkers, and endothelial function. The purpose of this study was to evaluate whether measures of exercise adherence were related to clinical outcome measures and indices of vascular health subsequent to a 6-month AEXT intervention in a middle-to-older aged African American cohort. Following dietary stabilization, sedentary, apparently healthy, African American adults (40 – 71 y/o) underwent baseline testing including blood pressure, flow-mediated dilation (FMD) studies, fasting blood sampling, and graded exercise testing. Upon completion of a supervised 6-month AEXT intervention, participants repeated all baseline tests. Exercise adherence was measured three ways: exercise percentage, exercise volume, and exercise score. There were no significant correlations between the changes in the vascular health biomarkers of the participants and any of the adherence measures. In addition, there were no significant correlations between any of the adherence measures and the clinical values of the participants that had been significantly changed pre-post-AEXT. Participants improved their clinical and vascular health and decreased risk factors for hypertension and cardiovascular disease regardless of their level of adherence to AEXT. Future studies should continue to accurately quantify adherence in order to assess the exercise dose for improvements in vascular and clinical health.